Etos dan Perilaku Produktif Siswa SMK Swasta X di Depok Jawa Barat - Arfian Arfian (Jurnal Ilmiah Wahana Pendidikan, 2023)
Abstract Indonesia will enter a demographic bonus in 2035: besides that, it is also in the implementation of industry 4.0, so a work ethic is needed to deal with this demographic bonus problem. Competition for human resources is quite tight, requiring each individual to improve human resource skills that are superior in various aspects. One of the efforts is to increase students' productive behavior. Student success is influenced by many factors, one of which is productive behavior. So this study aims to determine the effect of work ethic on students' productive behavior. The research sample was students of grades 11 and 12 of Private Vocational High School X Depok, totaling 214 students. This study used a quantitative approach, so data collection was carried out using a questionnaire/instrument measuring the work ethic and the productive behavior variables. Likert scale model with four alternative answers. Data were analyzed using SEM-lisrel series 8.8. The results of research on work ethic affect productive behavior; the higher the work ethic, the higher the productive behavior.